Computational aeroacoustics beneath high speed transitional and turbulent boundary layers. (15th May 2020) - Ritos, Konstantinos; Drikakis, Dimitris; Kokkinakis, Ioannis W.; Spottswood, S. Michael
Highlights: Investigation of pressure fluctuations beneath a hypersonic boundary layer. Influence of shock-boundary layer interaction in pressure fluctuations. Analysis of pressure spectra and acoustic loading for hypersonic flow. High-resolution implicit Large Eddy Simulation for hypersonic turbulent flow. Abstract: This paper concerns a study of pressure fluctuations beneath hypersonic shock-wave turbulent boundary layer interactions and the associated acoustic loading on a compression/expansion ramp. Using high-order methods, we have performed Direct Numerical Simulations at Mach 7.2. We compare the spectral analysis of the pressure fluctuations at various locations of the compression/expansion ramp with the spectra calculated beneath a hypersonic transitional boundary layer. Similarities and differences between the two hypersonic boundary layers, in the context of acoustic loading, are drawn. Extremely high values of pressure fluctuations are recorded after the shock re-attachment where we also observe the maximum pressure gradients indicating that acoustic loading is correlated with areas of high-pressure gradients. Finally, we discuss the impact of the boundary layer state (attached flow, turbulence bursts, recirculations, shock oscillations, shock re-attachment and expansion fans) on the frequency spectrum of the pressure fluctuations.